Адаптація аутсорингових моделей в електроній комерції до умов глобальної диджіталізації - Сергієнко, Олена Андріанівна; Бріль, М. С.; Бабенко, Максим Віталійович (My University, 2025)
У статті досліджено особливості адаптації аутсорсингу в електронній комерції до умов глобальної диджіталізації. Доведено, що процеси диджіталізації можна вважати глобальним трендом, пов’язаним із впровадженням цифрових технологій у всі сфери життя. Встановлено, що диджиталізація стимулює оптимізацію бізнес-процесів, сприяє підвищенню ефективності функціонування підприємств, зокрема, у сфері електронної комерції. Водночас, вона створює додаткові виклики для підприємств, вимагаючи від них адаптації до нових умов. Мета статті полягає у проведенні аналізу сучасних аутсорсингових моделей в системі електронної комерції та визначенні можливостей їхнього застосування з метою адаптації до умов диджіталізації. Проаналізовано напрями адаптації основних моделей аутсорсингу в електронній комерції з врахуванням поширення цифрових технологій.

The article examines the features of the adaptation of outsourcing in e-commerce to the conditions of global digitalization. It is proven that digitalization processes can be considered a global trend associated with the introduction of digital technologies into all spheres of life. It is established that digitalization stimulates the optimization of business processes, contributes to increasing the efficiency of the functioning of enterprises, in particular, in the field of e-commerce. At the same time, it creates additional challenges for enterprises, requiring them to adapt to new conditions. Most business entities are forced to transform their business taking into account the impact of digital technologies in order not to gradually lose their positions in the market. The purpose of the article is to analyze modern outsourcing models in the e-commerce system and determine the possibilities of their application in order to adapt to the conditions of digitalization. A review of scientific works by domestic and foreign scientists devoted to the study of the features of outsourcing as a specific model of business process optimization is carried out. It was found that scientists focused their attention on highlighting the advantages and disadvantages of outsourcing, its impact on the functioning of companies and their efficiency. The need for careful study of the directions of outsourcing transformation in e-commerce in order to adapt to new operating conditions associated with digitalization was proven. The main prospects for the further development of the global outsourcing market were considered according to the conclusions of leading analysts. It was determined that stable growth in market volumes is predicted in the next ten years. The main models of outsourcing in e-commerce were determined. The directions of adaptation of the main outsourcing models in e-commerce were analyzed, taking into account the spread of digital technologies. It was proven that outsourcing services are becoming an integral tool for optimizing business processes in e-commerce.
Adaptation of outsourcing models in electronic commerce to the conditions of global digitalization
Keywords: електронна комерція; диджиталізація; цифрові технології; аутсорсинг; аутсорсингові моделі; адаптація; e-commerce; digitalization; digital technologies; outsourcing; outsourcing models; adaptation